From monologue to dialogue: Opening teachers' minds to authentic interaction with students. - Studer, Patrick; Kelly, Paul (Journal of Multilingual Theories & Practices, 2023)
Interaction undoubtedly is key to learning in higher education. It is particularly relevant in an English medium instruction (EMI) setting when students use a foreign language for learning as it provides important opportunities for the negotiation of meaning. In this article, we present and critically discuss EMI teacher training interventions in Switzerland designed to encourage dialogic interaction in the EMI classroom. EMI teacher training interventions, in the case of this study, rely on the EMI teaching competence reference framework outlined in Studer (2018). Through observations, (self-)assessments and surveys, teachers are assessed against four levels of attention to language in their classes, ranging from a focus on mutual comprehension to dialogue and the formal integration of language into the content of their classes. The paper shows that many EMI teachers tend to be more concerned with basic language and monologic competence, while sidelining dialogic competence. The paper will also show that the mental switch required to move the focus from 'stage performance' and self-awareness to authentic dialogue represents a significant challenge for our training programmes.